Security and Usability: Analysis and Evaluation. - Kainda, R; Flechais, I; Roscoe, A (IEEE, 2010)
The differences between the fields of Human Computer Interaction and Security (HCISec) and Human Computer Interaction (HCI) have not been investigated very closely. Many HCI methods and procedures have been adopted by HCISec researchers, however the extent to which these apply to the field of HCISec is arguable given the fine balance between improving the ease of use of a secure system and potentially weakening its security. That is to say that the techniques prevalent in HCI are aimed at improving users' effectiveness, efficiency or satisfaction, but they do not take into account the potential threats and vulnerabilities that they can introduce. To address this problem, we propose a security and usability threat model detailing the different factors that are pertinent to the security and usability of secure systems, together with a process for assessing these. © 2010 IEEE.